1970
DOI: 10.1530/jrf.0.0220213
|View full text |Cite
|
Sign up to set email alerts
|

Male Antifertility Compounds: U-5897 as a Rat Chemosterilant

Abstract: Summary. U-5897 (3-chloro-1,2-propanediol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 8 publications
1
42
0
Order By: Relevance
“…Approximately five times the MED of either compound will, however, produce a lesion in the caput epididymidis of the rat. This prevents spermatozoa from entering the epididymis and proper removal of testicular fluids causing testicular swelling and some alteration in spermatogenesis (Ericsson, 1970). However, epididymal lesions were not induced in guinea-pigs even at doses which ultimately caused death.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately five times the MED of either compound will, however, produce a lesion in the caput epididymidis of the rat. This prevents spermatozoa from entering the epididymis and proper removal of testicular fluids causing testicular swelling and some alteration in spermatogenesis (Ericsson, 1970). However, epididymal lesions were not induced in guinea-pigs even at doses which ultimately caused death.…”
Section: Methodsmentioning
confidence: 99%
“…In the rabbit, spermatozoa from the caput epididymidis are incapable of fertility (Bedford, 1966(Bedford, , 1967Orgebin-Crist, 1967 (Mason & Young, 1967) and is perhaps more vulnerable to these drugs because of the sluggishness of blood flow (see Ericsson (1970) for a more complete review of this phenomenon). The resultant conditions yield spermatozoa incapable of performing their normal function of fertilizing ova, which is supported by the absence of spermatozoa on recovered uncleaved ova.…”
Section: Methodsmentioning
confidence: 99%
“…It frequently induces pathological changes in the epididymis, culminating in cyst formation in this duct on one or both sides (Cooper & Jackson, 1970). Ericsson (1970) found that a-chlorhydrin (U-5897) caused cysts in the rat, specifically in the ductuli efferentes and initial part of the caput epididymidis, which led to permanent sterility. Recently, Ericsson (1971) (Clermont & Flannery, 1970 (Cooper & Jackson, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Fifty percent of rats given a single large dose of 6 CDG (250 mg/kg) developed spermatocoeles which were identical in appearance to those produced by «-chlorohydrin (Ericsson, 1970 ;Hoffer et al, 1973 …”
mentioning
confidence: 87%